Menjaga Berkah di Era Digital: Strategi Perbankan Syariah Menghadapi Disrupsi AI dan Gen-Z - Awaluddini Marifatullah; Lika Akana Helmi; Abdul Rahim (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2026)
The integration of Artificial Intelligence (AI) and the expansion of Generation Z (Gen-Z) pose dual challenges and transformative opportunities for the Islamic banking industry. This study aims to formulate a digital strategy to maintain Sharia compliance and market competitiveness. Using a descriptive-qualitative library research approach, this paper evaluates technology adoption through TAM, UTAUT, Institutional Theory, and Maqashid al-Shariah frameworks. The findings highlight a critical market mismatch: while Gen-Z accounts for 24.93% of Indonesia's 284.67 million population, the Islamic banking market share stagnates at 7.51% due to low financial literacy. As digital natives, Gen-Z demands high performance expectancy, rapid access, and robust cybersecurity to prevent data breaches. Consequently, this study proposes a "Dual-Engine Transformation" strategy. Engine 1 leverages advanced AI for objective operational efficiency and algorithmic re-engineering to support wealth protection (Hifzh al-Mal). Engine 2 digitizes Islamic social finance (ZISWAF) and halal lifestyles to drive public welfare (Hifzh al-'Aql). Ultimately, implementing digital Sharia governance driven by Sharia IT Auditors and Algorithmic Sharia Certifications is vital to ensuring transactional sanctity (barakah) in an automated era.